A two-step process coupling photocatalysis with adsorption to treat tetracycline - Copper(II) hybrid wastewaters. (June 2022) - Gong, Yinan; Wang, Ying; Tang, Miaomiao; Zhang, Hao; Wu, Pan; Liu, Changjun; He, Jian; Jiang, Wei
Abstract: The rapid development of large-scale animal husbandry has led to an increase in the quantities of tetracycline (TC), Cu(II) and pollutants resulting from the complexation of these substances in wastewater, that is severely damaging to the environment. Novel environmental technology to treat TC-Cu(II) mixed polluted wastewater is urgently required. In this study, a novel process was developed combining TiO2 photocatalysis with TP207 adsorption to treat TC-Cu(II) mixed wastewater and recover copper resources. The concentrations of TC and Cu(II) in the treated wastewater were 1.1 mg/L and 0.2 mg/L, respectively, meeting emission standards. The copper recovery efficiency for TP207 desorption reached 81%. Both TiO2 and TP207 maintained good stability over five treatment cycles. The TC-Cu(II) mixed wastewater was treated without any harmful effects, and copper resources were recovered using the aforementioned combined process. An alternative treatment for mixed wastewater containing antibiotics and heavy metals was proposed in this study.